Gen-Z and VAT Rate Changes: Assessing the Impact on VAT Revenue Potential in Indonesia - Rusli, Yohanes Mardinata; Hakki, Tandry Whittleliang; Surjadi, Merna (Eastasouth Institute, 2025)
This study aims to examine the effect of the VAT rate increase and tax literacy in Indonesia, especially in Jakarta, for taxpayers with age groups, especially among Generation Z (Gen-Z) on the potential for Value Added Tax (VAT) revenue. This study uses primary data by distributing questionnaires to 200 taxpayers who are still included in the Gen-Z age group. The research sample was determined using a purposive sampling method. Data were analyzed using multiple linear regression analysis, assisted by IBM SPSS Statistics 26.00 software. The results of this study indicate that the increase in the Value Added Tax rate and tax literacy partially have a significant and positive effect on the potential for Value Added Tax revenue. This study has limitations in that it only took samples from taxpayers from the Gen-Z generation and only those domiciled in Jakarta.